2016
DOI: 10.18805/ajdfr.v35i4.6627
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physico-chemical properties of mix on the final quality of ice-cream

Abstract: The impact of physico-chemical properties of mix is carried forward in handling of mix, processing including freezing and quality of finished product. With precaution in selection and balancing ingredient viz. Fat, Protein, sugar along with emulsifier, stabilizer and various flavouring components may provide the better quality of the final product. The proper proportion of different ingredients, improved processing can provide better quality and lower cost of Ice-cream with appreciable and acceptable quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
5
4
Order By: Relevance
“…Melting rates were also higher in T1 and PT2 samples than in C and PC samples, with the differences being signi cant only when compared to the C sample (p < 0.05). These ndings contradict previous ndings (Bajad et al, 2016;Wu et al, 2019), which indicated that the melting rate of ice cream decreases with increasing overrun and fat destabilization. The larger volumes of air present in high overrun products resulted in a slower rate of heat transmission, resulting in slower melting rates (Muse and Hartel, 2004;Bajad et al, 2016).…”
Section: Meltingcontrasting
confidence: 99%
See 1 more Smart Citation
“…Melting rates were also higher in T1 and PT2 samples than in C and PC samples, with the differences being signi cant only when compared to the C sample (p < 0.05). These ndings contradict previous ndings (Bajad et al, 2016;Wu et al, 2019), which indicated that the melting rate of ice cream decreases with increasing overrun and fat destabilization. The larger volumes of air present in high overrun products resulted in a slower rate of heat transmission, resulting in slower melting rates (Muse and Hartel, 2004;Bajad et al, 2016).…”
Section: Meltingcontrasting
confidence: 99%
“…These ndings contradict previous ndings (Bajad et al, 2016;Wu et al, 2019), which indicated that the melting rate of ice cream decreases with increasing overrun and fat destabilization. The larger volumes of air present in high overrun products resulted in a slower rate of heat transmission, resulting in slower melting rates (Muse and Hartel, 2004;Bajad et al, 2016). The same pattern did not appear in CCE-containing ice creams with high overrun.…”
Section: Meltingcontrasting
confidence: 99%
“…Such results were observed in ice cream mixtures containing cress seed mucilage, flaxseed mucilage or guar gum (Abd El-Aziz et al, 2015), tiger nut aqueous extract (El-Shenawy et al, 2016) and food binders (Alakali et al, 2009). Bajad et al (2016) reported that the ice cream mixture is not a Newtonian fluid, pseudo-plastic behavior, where the viscosity decreases as the shear rate increases. However, the addition of CGBJ had a positive effect on the viscosity of the mixture, which increased proportionately with the concentration of CGBJ.…”
Section: Ice Cream Mixture Propertiesmentioning
confidence: 99%
“…Marshall et al (2003) observed that, as the viscosity increases, the rate of whipping decreases due to the weakening air incorporation. Bajad et al (2016) reported that if the liquid is too viscous, it is difficult to integrate the air. Also, a high acidity content induced fat destabilization that was better characterized as coalescence, leading to a decrease in overrun percentage.…”
Section: Frozen Ice Cream Propertiesmentioning
confidence: 99%
See 1 more Smart Citation